Measuring the impact of fiscal policy of posting from Romania to European Union - Elena HLACIUC; t Daniel RAȚĂ (USV Annals of Economics and Public Administration, 2019)
Despite the heated debate on the negative consequences of posting in host countries, the profile and impact of this phenomenon have not yet been mapped in detail. For example, to date there is no further breakdown of the subsectors in the industries where the workers are posted. The question is also whether posting causes a shift in internal jobs in each sub-sector. At the same time, information on economic entities using posted workers' services, which is the profile of internal labor force companies vs. the profile of those who prefer posted workers. The European Union has developed employment protection or job creation policies but it has not yet been possible to harmonize fiscal policies with a view to the application by all Member States of a unified fiscal policy on direct taxation. Tax reforms differ from one Member State to another in scope and depth, but their main objective is to reduce the tax burden, especially for low wage staff. In this paper is highlight the necessity of a harmonization regarding the posting in EU, and I hope that this study will help the company and its accountants to understand better the fiscal interpretation of posting from Romania in another country from European Union.